XSS attacks : cross-site scripting exploits and defense - Grossman, Jeremiah (Syngress, 2007)
Cross Site Scripting Attacks starts by defining the terms and laying out the ground work. It assumes that the reader is familiar with basic web programming (HTML) and JavaScript. First it discusses the concepts, methodology, and technology that makes XSS a valid concern. It then moves into the various types of XSS attacks, how they are implemented, used, and abused. After XSS is thoroughly explored, the next part provides examples of XSS malware and demonstrates real cases where XSS is a dangerous risk that exposes internet users to remote access, sensitive data theft, and monetary losses. Fin.